The complementarity of humility hypothesis: Individual, relational, and physiological effects of mutually humble partners. Issue 2 (4th March 2019) - Van Tongeren, Daryl R.; Hook, Joshua N.; Ramos, Marciana J.; Edwards, Megan; Worthington, Everett L.; Davis, Don E.; Ruiz, John M.; Reid, Chelsea A.; Garthe, Rachel C.; Nonterah, Camilla W.; Cowden, Richard G.; Opare-Henaku, Annabella; et al.
Abstract: We report two studies of romantic couples that examine the interactive effects of actor and partner humility on individual, relational, and physiological well-being. Using both longitudinal (Study 1) and physiological (Study 2) methods from two samples of romantic couples, we explored the interactive effects of actor and partner humility. Individuals in dyads with complementary high humility reported better mental health over time following a major life transition, the birth of their first child, in Study 1 and higher relationship satisfaction and lower physiological responses (i.e. blood pressure) following the discussion of a topic of disagreement in Study 2. These results suggest that being humble is beneficial when one has a humble partner, but being arrogant – especially within a disagreement with one's partner – could undermine the benefits of humility. That is, the benefits of humility are greatest in dyads in which both partners are humble.